Determining the Foreign Currencies Affecting the Bitcoin. - Ozaltun, Gul Cennet; Ege, Ilhan; Topaloglu, Emre E.; Huang, Chiahsing; Ürkmez, Taylan (Sciendo, 2023)
In the present paper, the Granger causality test is used to study the causality relationships between Bitcoin and some of the most highly traded currencies, including euro, Japanese yen, British pound, Chinese yuan, and Indian rupee. To this purpose, the daily exchange rates of Bitcoin and the selected currencies to USD between 2014 and 2018 were used. Different from findings in existing literature, our study shows that there are no Granger causalities between Bitcoin and Euro, Japanese yen, British pound, and Indian rupee. A Granger causality is found in the direction from the Chinese yuan to Bitcoin. © 2023 Gul Cennet Ozaltun et al., published by Sciendo.
Keywords: Bitcoin; Cryptocurrency; Electronic Money; Exchange Rate; Granger Causality; Time Series Analysis